End-of-Life Care and Use of Hospital Resources in Radiotherapy-Treated Cancer Patients with Brain Metastases: A Single-Institution Retrospective Study - Nåhls, Nelli-Sofia; Anttonen, Anu; Löyttyniemi, Eliisa; Jekunen, Antti; Akrén, Outi; Saarto, Tiina (MARY ANN LIEBERT, INC, 2025)
Purpose: The aim of this single-institution retrospective study of patients treated with radiotherapy for brain metastases (BM) was to evaluate the timing of the palliative care (PC) decision, the use of health care services, i.e., emergency department (ED) visits and hospitalizations, and the implementation of radiotherapy at the end of life (EOL).
Methods: Data on all cancer patients with BM treated in Finland at the Vaasa Central Hospital Radiotherapy Department between March 2011 and November 2020 were retrospectively reviewed. The follow-up period lasted until November 2021. Altogether, 91 patients (54 men, mean age 67 years [range 23-91 years]) were analyzed. Data on timing of PC decision, visits to the PC outpatient unit, and ED and hospitalization periods were collected retrospectively from patients' records.
Results: The median overall survival from diagnosis of BM was 3.7 months (range 1-62 months) and, after radiotherapy, 2 months (0-61 months). Thirty-two percent of the patients received radiotherapy in the last month of life. During the last 30 days of life, 44 patients (48%) visited the ED and 38 (42%) were hospitalized. Patients with an early PC decision (>30 days before death) had fewer hospitalizations (22% vs. 53%; p = 0.005) and died less often during the hospitalization period (9% vs. 27%; p = 0.047) at EOL. No significant difference was found in ED visits (41% vs. 53%; p = 0.28).
Conclusion: For a large proportion of patients with BM, the prognosis is very poor. It is important to identify these patients and abstain from radiotherapy at EOL to reducing inappropriate health care utilization.